SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN PESERTA COMPETENCE AID PROGRAM DI ASTRAGRAPHIA DENGAN METODE SAW - Dian Gustina; Ibnu Fauzi Meirianto (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2018)
The process of receiving training CAP participants can be an error in determining the participants who are eligible to join in the training. This can happen because of the number of assessment criteria and participants who register, meanwhile the participants received only 10 people. The purpose and writing of this final task is to produce a decision support system of cap participant acceptance in astragraphia, which can help in determining the participants who are entitled to the training and also the acceptance decision is more grounded because it has passed the calculation stage according to the existing criteria. System development method used is System Development Life Cycle (SDLC). Starting from the stage of needs analysis, design, coding, and testing. the method for the calculation of decision support system used is Simple Additive Weigthing method (SAW), because this method can distinguish different calculations between attributes cost and benefit. The results of the application test show that the functionality of the application is in accordance with what is planned and issued the expected output